1995
DOI: 10.1002/1097-0142(19951201)76:11<2375::aid-cncr2820761129>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists and primary care physicians' attitudes toward pain control and morphine prescribing in france

Abstract: Background. Two representative samples of primary care physicians (N=600) and medical oncologists (N=300) in France were surveyed about their attitudes toward and knowledge about cancer pain management. Methods. The survey was conducted by telephone with a questionnaire based on a model developed by the University of Wisconsin‐Madison Pain Research Group. It was designed to assess physicians' estimates of the prevalence of pain among patients with cancer, their practice in prescribing analgesics, their trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0
5

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 15 publications
7
89
0
5
Order By: Relevance
“…A substantial 42% of respondents reported that they had not received adequate training in palliative care during their residency training. This finding is consistent with previously published data regarding the training of medical oncologists in the management of cancer pain, [17][18][19] communication skills, 20,21 and palliative care. 19,22 2) In response to the statement, "most medical oncologists I know are expert in the management of the physical and psychological symptoms of advanced cancer," more respondents disagreed (41.8%) than agreed (37.5%).…”
Section: Discussionsupporting
confidence: 93%
“…A substantial 42% of respondents reported that they had not received adequate training in palliative care during their residency training. This finding is consistent with previously published data regarding the training of medical oncologists in the management of cancer pain, [17][18][19] communication skills, 20,21 and palliative care. 19,22 2) In response to the statement, "most medical oncologists I know are expert in the management of the physical and psychological symptoms of advanced cancer," more respondents disagreed (41.8%) than agreed (37.5%).…”
Section: Discussionsupporting
confidence: 93%
“…47 50,63 ; however, about half felt unprepared to manage longterm side-effects 40 or conduct surveillance for recurrence. 60 In general, high levels of confidence were reported for tasks such as pain management, 55 conveying bad news 71 and psychological support. 50,63,64,67 However, lower levels of training or knowledge were reported for areas such as surveillance testing, 60 active treatment or surgery 38,54 and advising on complementary therapies, 61 leading to a reluctance to fulfil such roles.…”
Section: Pcp Preferences For Models Of Carementioning
confidence: 99%
“…It appears that PCP confidence levels fluctuate along the cancer care continuum and according to the type of care needed. High confidence was reported for non-cancer specific tasks such as pain management and psychosocial support, 50,55,63 while confidence was lower for active treatment, surveillance testing and management of long-term effects, 38,40,54,60 suggesting PCPs are willing but feel unprepared to manage certain aspects of cancerspecific care. This may be attributed to PCPs' reports of minimal formal training in survivorship care, the lack of appropriate guidelines, insufficient contact with oncologists and insufficient experience.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Doctors with more prejudice about opioids were women and older oncologists. 49 Varela & Aubry revealed, also in France, that more than 60% of doctors thought that morphine had a ceiling dose. 50 As per 1 082 dying patients, French GP and oncologists prescribe opioids in 85.4% of them.…”
mentioning
confidence: 99%
“…48 In France, 76% of 600 GP and 50% of 300 oncologists were reluctant to prescribe morphine. 49 Both groups mentioned fear of side effects as the main reason, as well as concerns about the risk of tolerance, morphine's poor public image and the constraints of prescription forms. Doctors with more prejudice about opioids were women and older oncologists.…”
mentioning
confidence: 99%